A Demographic Framework for the 1932–1934 Famine in the Soviet Union. Issue 4 (2nd October 2021) - Wolowyna, Oleh
ABSTRACT: Research on the 1932–1934 famine in the Soviet Union (or Famine) has reached the point where some analytical and theoretical synthesis is needed. We present a framework that provides a structure for organizing demographic research of the Famine within a broader demographic-historical context. Elements of the framework are: (a) definitions of critical concepts (Famine, Holodomor, Famine losses); (b) population reconstruction methodology as a basis for estimating Famine losses; (c) a formal structure that facilitates comparative research of the Famine among different subpopulations; (d) elements of an integrated demographic-historical research strategy; (e) recommendations for quantification in historical research. The presentation of the framework is preceded by: (a) examples of the versatility of the population reconstruction methodology; (b) analysis of what is probably a unique characteristic of the Famine, i.e. the surge in rural mortality during the first half of 1933 in regions of Ukraine and Russia, resulting in about seventy to eighty per cent of all Famine losses concentrated in that period; (c) formulation of an analytical model of this surge as an example of an application of the framework. We show significant differences in the rural mortality surges between Ukraine and Russia, e.g.: (a) in two oblasts of Ukraine the number of losses in June 1933 is fourteen to fifteen times higher than in January of that year, compared to a maximum factor of eight in only one region of Russia; (b) the average number of daily losses at the peak of the Famine in Ukraine, June 1933, is 28, 000, while the respective number in Russia is 12, 000 in July 1933. Standardizing by population size, we have 12.4 daily losses per 1, 000 population in Ukraine and 1.4 in Russia. Several examples illustrate the advantages of a collaborative demographic-historical research strategy.